PEMBENTUKAN INGO (KATA SANDI) DALAM DUNIA KEPOLISIAN JEPANG - Taqdir Taqdir (IZUMI, 2016)
The purposeof this studywas to determinethe structure offormingingo(argot), especially in the Japanesepolice. The data werederivedfromthe expressions(argot) that isoften used inthe Japanesepolice. The analysis inthis studyrefersto the theory ofthe formation ofthedividingMikatastructureformationin tensections, while analysisrefersto the theoryof meaningArgot’sSanada.Finding in this study is thatthe formation ofthe policeargotinJapaninclude the establishment ofshorteningsyllables, syllableexchange, a similar shape, association, movement, imagery, soundthe same, the gameof letters, symbols, andanalogies